Motivasi dan Disiplin Kerja Pada Kinerja Perangkat Desa Dengan Metode Partial Least Square - Rismayanti, Ema; Akbar, Gugun Geusan; Hakim, Bani Lukmanul (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
Management of government resources is a major factor in realizing good service in the public sector. However, in this study village officials still need to improve their performance which is closely related to discipline and motivation as the reason for the successful performance of village officials. The purpose of this research is to prove motivation and discipline on performance. Quantitative approach with Partial Least Square is a method of data analysis. The sample in this study were 93 people by removing porposive random sampling. From the results of data analysis, it is stated that motivation and discipline simultaneously have a significant effect on performance. The prediction model from the results of this study is able to explain the performance variable of 96.2% (R2 = 0.9624)